PEMIKIRAN FIQH PROGRESIF UMAR IBN AL-KHATTHAB - Nawawi (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
Many people consider that Umar was an independent and critical thinkerin Islam, who introduced a dynamic face of Islamic law as a result of thechanging era. His methods of legal-reasoning (ijtihad) used rationalitymore often rather than the popular way of thinking by approaching thedhanny aspects of nash in Qur’an or Sunnah. Umar’s epistemology isijtihad with maslahat as he views that maslahat can take place in the lawitself. Umar believes that law may change due to the change of thesituation. In fact, the change is in line with maqashid al-syariah asphilosophical value of a law. The change is not the the syariah, but itsimplementation establishes the maslahah as the main standard. WhenUmar’s ijtihad seems to be in contrary with the fixed and clear nash, itdoes not mean that he sidelined and ignored the nash, but he appliedtakhshsish, such as takhshish bi al mashlahah, takhshish bi mabadi’ asysyari’ah wa maqashidihi al-‘ammah and takhshish bi hikmah at-tasyri’.